Analysis of Menstrual Periods, Menstrual Cycle, Menstrual Pain and Body Mass Index with the Incidence of Anemia in Adolescent Girls - Karinda, Merlin; Lellyawaty, Lellyawaty; Vaira, Rizky (Biomedical Journal of Indonesia, 2025)
Introduction. Periodic blood loss due to menstruation makes adolescent girls more susceptible to anemia. Menstrual periods such as prolonged menstruation, irregular monthly cycles, volume of blood loss, and health problems that accompany menstruation such as menstrual pain coupled with nutritional status can affect the occurrence of anemia in adolescents. The purpose of the study was to determine the relationship between menstrual periods, menstrual cycle, menstrual pain, and BMI with the incidence of anemia. Methods. This study was a cross-sectional study with a sample size of 53 respondents of adolescent girls of the Mambaul Ulum Islamic Boarding School in Banjarmasin City using an accidental sampling technique and analyzed using chi-square. The study was conducted in July 2024. The respondent’s height was measured using a microtoise and weight using a scale. Furthermore, they filled out a questionnaire about the menstrual periods, menstrual cycle, and menstrual pain, and the hemoglobin levels were checked using the Easytouch tool. Results. There was a relationship between BMI and anemia with a p-value of 0.026. Conclusion. It is important to provide education about understanding good and sufficient eating patterns and nutrition, as well as education about the importance of taking iron tablets and education about the side effects of iron tablets in an effort to prevent anemia.